Pytheas the Massaliot and the Baltic. Myth or Reality? - Tillisch, Søren Skriver (Archaeologia Lituana, 2022)
Pytheas the Massaliot travelled the entire European coastline from Gades (Cadiz) to the mythological northern mouth of the Tanais (Don), circumnavigated Britain, reached ultima Thule, probably the Faroes, and the amber island of Abalus, probably Thy, and Norway, possibly the land of the Periscians. This article revisits the idea of Pytheas reaching the Baltic, very possibly the area of the northern mouth of Tanais (Vistula? Nemunas?), and the idea of Kaali on Saaremaa as “the place where the sun went to bed”’. The examination of the question is introduced with a historiographical excursus and chapters on the scientific background of the journey, the measurements of Pytheas, his hometown Massalia and his journey as far as the Western Baltic. The argument will be exposed through analysis and comparison of the archaeological and written evidence. In conclusion it is argued that Kaali on Saaremaa was visited by Pytheas the Massaliot and may indeed be considered “the place where the sun went to bed” but not “ultima Thule”.